The value of a learning needs analysis to establish educational priorities in a new clinical workforce. (March 2018) - Hudson, Adrienne; Ellis-Cohen, Elayne; Davies, Shari; Horn, Desley; Dale, Alison; Malyon, Lorelle; Edwards, Rachel; Harnischfeger, Jane; Radel, Glenda; Bundy, Rebecca; Jauncey-Cooke, Jacqueline
Abstract: A learning needs analysis was undertaken in a newly formed workforce. The goal of the learning needs analysis was to establish both the skill set and educational needs in the nursing workforce prior to moving to a new purpose built facility. The results would then enable nurse educators to develop, plan and deliver appropriate educational strategies. Staff (73%) completed an online survey; the results were collated and analysed. The results of the learning needs analysis suggested an experienced workforce that had great capacity to care for children across a wide spectrum of acute clinical needs. Interestingly the results of the learning needs analysis conflicted with the clinical reality. To investigate possible reasons for this difference we conducted a focus group session with nurse educators. The focus group findings highlighted the significance of change and how that impacted on the clinical capacity of experienced staff. We concluded that the results of the learning needs analysis were representative however they needed careful interpretation in the context of substantial change. Highlights: Learning needs analyses provide information on clinical skill sets and deficits. Substantial change impacts significantly on nursing capacity. Reduced capacity is a temporary aberration.